Data Poor Approach for the Assessment of the Main Target Species of Rapido Trawl Fishery in Adriatic Sea - Armelloni, Enrico Nicola; Scanu, Martina; Masnadi, Francesco; Coro, Gianpaolo; Angelini, Silvia; Scarcella, Giuseppe (Frontiers in Marine Science, 2021)
Information on stock status is available only for a few of the species forming the catch assemblage of rapido fishery of the North-central Adriatic Sea (Mediterranean Sea). Species that are caught almost exclusively by this gear, either as target (such as Pectinidae) or accessory catches (such as flatfishes apart from the common sole), remain unassessed mainly due to the lack of data and biological information. Based on cluster analysis, the catch assemblage of this fishery was identified and assessed using CMSY model. The results of this data-poor methodology showed that, among the species analyzed, no one is sustainably exploited. The single-species CMSY results were used as input to an extension of the same model, to test the effect of four different harvest control rule (HCR) scenarios on the entire catch assemblage, through 15-years forecasts. The analysis showed that the percentage of the stocks that will reach Bmsy at the end of the projections will depend on the HCR applied. Forecasts showed that a reduction of 20% of fishing effort may permit to most of the target and accessory species of the rapido trawl fishery in the Adriatic Sea to recover to Bmsy levels within 15 years, also providing a slight increase in the expected catches.